Problem Solving Ability of Junior High School Students Towards Geometry: Gender and Mathematical Disposition Analysis - AB, Joko Sutrisno (FKIP Universitas Lampung, 2019)
Problem solving ability of Junior High School students towards geometry: Gender and mathematical disposition analysis. Objectives: The purpose of this study aimed to analyze the effect of gender and mathematical disposition towards the problem-solving ability of geometry at Junior High School students in Bandar Lampung City. Methods: The study used a survey method with two-way analysis of variance. Gender and mathematical disposition are independent variables, while the problem-solving ability of geometry is dependent variables. Findings: The results showed that there was no difference in the average of the problem-solving ability of geometry between male students and female students. Moreover, there was no interaction effect gender and mathematical disposition towards the problem-solving ability of geometry. Last, the average the problem-solving ability of geometry of students who had a high mathematical disposition was higher than students who had a low mathematical disposition. Conclusions: The difference in geometry problem-solving ability occured in male and female students. Keywords: Problem-solving ability, geometry, gender, mathematical disposition. DOI: http://dx.doi.org/10.23960/jpp.v9.i2.201923